Effects of different exercise training programs on post-exercise $$\dot{{\varvec{V}}}$$O2 recovery responses in patients with coronary heart disease - Mathieu Gayda; Lukas-Daniel Trachsel; Florent Besnier; Maxime Boidin; Julie Lalongé; Louis Bherer; Martin Juneau; Pierre-Marie Leprêtre; Anil Nigam (European Journal of Applied Physiology, 2026)

Mitochondrial respiratory capacities are not linked to individual variation in hypoxia tolerance and standard metabolic rate in European seabass Dicentrarchus labrax - Elisa Thoral; Julie Nati; Jean‐Baptiste Quémeneur; Léann Lozac'h; Germain Salou; Alain Vergnet; Mathieu Besson; Marc Vandeputte; François Allal; Karine Salin; David J. McKenzie; Loïc Teulier (Journal of Fish Biology, 2026)
In hypoxic environments, fish attempt to regulate their metabolic rate as oxygen levels in the water decline. Individuals that have low energy requirements for maintenance – standard metabolic rate (SMR) – are expected to have higher hypoxia tolerance, measured as the critical water oxygen saturation threshold (S crit ) below which they cannot regulate SMR. These whole animal traits may, in turn, be linked to aspects of individual mitochondrial oxidative metabolism that underpin SMR. We therefore investigated, in European seabass Dicentrarchus labrax , whether inter‐individual variation in SMR and S crit , measured by whole animal respirometry, was correlated with elements of mitochondrial metabolism in liver and heart, measured by high resolution respirometry (HRR). Among the 96 fish studied, inter‐individual variation in S crit was dependent upon variation in SMR. However, there was no evidence for correlations between SMR or S crit and individual mitochondrial respiratory capacities. Our results indicate that individual variation in complex whole animal traits of respiratory metabolism cannot always be linked to variation in subcellular mitochondrial phenotypes.

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Evaluation of the potential environmental impacts and benefits of producing alkali-activated concrete from bauxite residue - Luciano Viana; João Augusto Lago Araújo Seixas; Pierre-Luc Dessureault; Julie-Élize Guérin; Esteban Gonzalez; Reza Jafari; Ahmed Rahem; Mathieu Fiset; Annie Levasseur; Jean-François Boucher (Journal of Cleaner Production, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Nutrients on the move: Investigating large scale fatty acid exports from European ponds via emerging insects - Lena Fehlinger; Fernando Chaguaceda; Pietro Tirozzi; Marina Tomás‐Martín; Ellinor Jakobsson; Teofana Chonova; Benjamin Misteli; Alberto Scotti; Jorge F. Henriques; Juan Rubio‐Ríos; Daniel Morant; Pierre Marle; et al. (Limnology and Oceanography, 2025)
Permanent ponds are key landscape units that supply various ecosystem services. Notably, the export of aquatic subsidies to land via emerging insects may significantly influence terrestrial food webs. Polyunsaturated fatty acids (PUFA), which enhance consumer fitness, are among the essential exported components. The patterns and drivers of dietary exports from ponds via insects remain poorly known, particularly at continental scales. We analyzed the exports of biomass, lipid, and fatty acid contents from emerging insects, sampled in 36 ponds across 11 European countries, from 36°N to 59°N and from 26°W to 19°E, over four seasons. We found that biomass and fatty acid exports decreased with increasing latitude and were higher in spring and summer. Seasonal effects also increased with higher latitudes. Temperature was the most important predictor of insect biomass, explaining 27.6% of the total variation and showing an unimodal response. Thus, increasing temperature may promote exports in colder regions and seasons but may negatively influence biomass exports in already warm regions. The exports of total lipids, PUFA, and eicosapentaenoic acid were correlated to exported biomass, while those of docosahexaenoic acid were linked to the emergence of Chaoboridae. Our findings indicated that PUFA contents were affected by taxonomic insect community composition and pond trophic state (indicated by chlorophyll a ). Two of the correlates identified here (temperature and trophic state) are influenced by anthropogenic activity via climate and land use change, respectively. Thus, human activity impacts the food webs in and around ponds by influencing the quantity and quality of nutritional exports.

Qualification of microclimate models and simulation tools: An academic benchmark - Teddy Gresse; Julie Soriano; Auline Rodler; Jean-Claude Krapez; Jean Pierro; Félix Schmitt; Mathieu Galtier; Frédéric André; Frédéric Kuznik; Lionel Soulhac; Damien David; Jérôme Jacob; et al. (Building and Environment, 2025)

Local, environmental and trace metal effects on gut microbiota diversity in urban feral pigeons - Clarence Schmitt; Julien Gasparini; Héloïse Moullec; Laurence Walch; Mathieu Leroux-Coyau; Julie Leloup (Environmental Research, 2025)

Corrigendum to “Pre-hispanic wetland irrigation and metallurgy in the South Andean Altiplano (Intersalar Region, Bolivia, XIVth and XVth century CE)” [Quat. Sci. Reviews 338 (2024) 108826] - Stéphane Guédron; Clément Roy; Géraldine Sarret; Julie Tolu; Marie-Pierre Ledru; Sylvain Campillo; Sarah Bureau; Anne-Lise Develle; Charline Guiguet-Covex; Eduardo Queiroz Alves; Mathieu Boudin; Richard Joffre; et al. (Quaternary Science Reviews, 2025)

Does Perceived Nuisance Abundance of Water Plants Match with Willingness-to-Pay for Removal? Contrasts Among Different User Categories - Jan E. Vermaat; Kirstine Thiemer; Bart Immerzeel; Susanne C. Schneider; Keneilwe Sebola; Julie Coetzee; Antonella Petruzzella; Samuel N. Motitsoe; Mathieu Baldo; Benjamin Misteli; Gabrielle Thiébaut; Sabine Hilt; et al. (Environmental Management, 2025)
Dense beds of water plants can be perceived as nuisance, but this perception, however, may not be similar for different user categories, and this may affect their willingness-to-pay (WTP) for plant removal. A questionnaire survey was used to test this for residents and visitors and find underlying socio-cultural or economic drivers. We studied five cases where nuisance water plant growth is managed: the rivers Otra (Norway) and Spree (Germany), and the lakes Kemnade (Germany), Grand-Lieu (France), and Hartbeespoort Dam (South Africa). We used a different payment vehicle for residents (annual household tax) and visitors (tourist tax). The survey included questions on days spent on specific types of activity per year, the importance attached to different functions and activities, overall environmental attitude, perception of the plants, socio-demographic respondent characteristics and WTP for increased plant removal. We observed no increase in WTP for increased removal in most sites. The two most important drivers of variation in current WTP were income, and whether respondents were engaged in boating and angling and thus perceived the plants negatively. Variation in WTP among sites was considerable, and mainly related to the mixture of activities among respondents. Differences between residents and visitors were less important than those among sites. Our observations bear importance for water management: information on differences in experienced nuisance among user categories and the frequency of use by these categories is useful as guidance for the design and implementation of any plant removal plan.

Innovative Pathways for the use of Excavation Materials in the Frame of the Future Circular Collider Project - Elisabeth Hauzinger; Luisa Ulrici; Johannes Gutleber; Robert Galler; Daniel Schneider; Maximilian Haas; Michael Benedikt; Mathieu Pillet; Jérémy Voiron; Pierre Boillon; Agathe Denot; Julie Paciello; et al. (Circular Economy and Sustainability, 2025)
Based a recommendation of the European strategy of particle physics of 2020 due to the great research success of the last decade CERN is planning a new circular collider with a circumference of approximately 91 km. To start construction in the middle 2030s a feasibility study is underway which includes scientific and financial components as well as territorial aspects such as geology, environment, technical infrastructure and civil engineering. One important factor is the management of the approximately 8 Mio. m3 of excavation materials, which consists mostly of molassic sediments of the Geneva Basin. In order to ensure that as much of the material as possible is put to high quality use in accordance with local regulations, the international contest “Mining the Future ® ” was launched. For this task geotechnical, mineralogical and geochemical tests were carried out on a large number of samples from across the study area. Based on the results, various utilization options were designed, which are primarily oriented towards alternative building materials with a low carbon footprint as well as agricultural use. The resulting concept of these sustainable strategies not only has a positive impact on the construction industry, but also play a major socio-economic role, as they improve social acceptance as well as responsibility in relation to large-scale projects.

Fate of chlordecone in soil food webs in a banana agroecosystem in Martinique - Mathieu Coulis; Julie Senecal; Yoann Devriendt-Renault; Thierry Guerin; Julien Parinet; Lai Ting Pak (Environmental Pollution, 2024)

Rhenium isotope variations in Icelandic groundwaters and hydrothermal systems - Wenhao Wang; Alexander J. Dickson; Mathieu Dellinger; Kevin W. Burton; Deirdre E. Clark; Guðjón Helgi Eggertsson; Íris Eva Einarsdóttir; Heimir Ingimarsson; Kiflom Gebrehiwot Mesfin; Robert G. Hilton; Julie Prytulak (Earth and Planetary Science Letters, 2024)

Pre-hispanic wetland irrigation and metallurgy in the South Andean Altiplano (Intersalar Region, Bolivia, XIVth and XVth century CE) - Stéphane Guédron; Clément Roy; Géraldine Sarret; Julie Tolu; Marie-Pierre Ledru; Sylvain Campillo; Sarah Bureau; Anne-Lise Develle; Charline Guiguet-Covex; Eduardo Queiroz Alves; Mathieu Boudin; Richard Joffre; et al. (Quaternary Science Reviews, 2024)

River flow intermittence influence biodiversity–stability relationships across spatial scales: Implications for an uncertain future - Andros T. Gianuca; Victor R. di Cavalcanti; Leonardo Cruz; Mathieu Floury; Julie Crabot; Laurent Valette; Jeremy Piffady; Thibault Datry (Global Change Biology, 2024)
Climate change is increasing the proportion of river networks experiencing flow intermittence, which in turn reduces local diversity (i.e., α‐diversity) but enhances variation in species composition among sites (i.e., β‐diversity), with potential consequences on ecosystem stability. Indeed, the multiscale theory of stability proposes that regional stability can be attained not only by local processes but also by spatial asynchrony among sites. However, it is still unknown whether and how scale‐dependent changes in biodiversity associated with river flow intermittence influence stability across spatial scales. To elucidate this, we here focus on multiple metacommunities of French rivers experiencing contrasting levels of flow intermittence. We clearly show that the relative contribution of spatial asynchrony to regional stability was higher for metacommunities of intermittent than perennial rivers. Surprisingly, spatial asynchrony was mainly linked to asynchronous population dynamics among sites, but not to β‐diversity. This finding was robust for both truly aquatic macroinvertebrates and for taxa that disperse aerially during their adult stages, implying the need to conserve multiple sites across the landscape to attain regional stability in intermittent rivers. By contrast, metacommunities of truly aquatic macroinvertebrates inhabiting perennial rivers were mainly stabilized by local processes. Our study provides novel evidence that metacommunities of perennial and intermittent rivers are stabilized by contrasting processes operating at different spatial scales. We demonstrate that flow intermittence enhances spatial asynchrony among sites, thus resulting in a regional stabilizing effect on intermittent river networks. Considering that climate change is increasing the proportion of intermittent rivers worldwide, our results suggest that managers need to focus on the spatial dynamics of metacommunities more than on local‐scale processes to monitor, restore, and conserve freshwater biodiversity.

Re-examining the earliest evidence of human presence in western Europe: New dating results from Pirro Nord (Italy) - Mathieu Duval; Lee J. Arnold; Jean-Jacques Bahain; Josep M. Parés; Martina Demuro; Christophe Falguères; Qingfeng Shao; Pierre Voinchet; Julie Arnaud; Claudio Berto; Gabriele Luigi Francesco Berruti; Sara Daffara; et al. (Quaternary Geochronology, 2024)

Engineering multi-degrading bacterial communities to bioremediate soils contaminated with pesticides residues - Sylvia Thieffry; Julie Aubert; Marion Devers-Lamrani; Fabrice Martin-Laurent; Sana Romdhane; Nadine Rouard; Mathieu Siol; Aymé Spor (Journal of Hazardous Materials, 2024)

Correction factors for large-scale greenhouse gas assessment from pulp and paper mill sludge landfill sites - Ranieri Ribeiro Paula; Mathieu Cusson; Normand Bertrand; Sylvie Bouchard; Martin H. Chantigny; Julie Lemieux; Emna Marouani; Claude Villeneuve; Patrick Faubert (Waste Management, 2024)

Do GC/MS methods available for furan and alkylfurans in food provide comparable results? – An interlaboratory study and safety assessment of 2-pentylfuran in food - Nancy Frank; Thierry Delatour; Mathieu Dubois; Ondrej Novotny; Thierry Dufossé; Julie Mollergues; Gabriele Scholz; Julie Moulin (Food Additives & Contaminants: Part A, 2024)

Derivation of Naïve Human Embryonic Stem Cells Using a CHK1 Inhibitor - Carol B. Ware; Erica C. Jonlin; Donovan J. Anderson; Christopher Cavanaugh; Jennifer Hesson; Sonia Sidhu; Savannah Cook; Guillermo Villagomez-Olea; Marshall S. Horwitz; Yuliang Wang; Julie Mathieu (Stem Cell Reviews and Reports, 2023)
Embryonic development is a continuum in vivo . Transcriptional analysis can separate established human embryonic stem cells (hESC) into at least four distinct developmental pluripotent stages, two naïve and two primed, early and late relative to the intact epiblast. In this study we primarily show that exposure of frozen human blastocysts to an inhibitor of checkpoint kinase 1 (CHK1) upon thaw greatly enhances establishment of karyotypically normal late naïve hESC cultures. These late naïve cells are plastic and can be toggled back to early naïve and forward to early primed pluripotent stages. The early primed cells are transcriptionally equivalent to the post inner cell mass intermediate (PICMI) stage seen one day following transfer of human blastocysts into in vitro culture and are stable at an earlier stage than conventional primed hESC. Graphical Abstract

Drivers of Perceived Nuisance Growth by Aquatic Plants - Kirstine Thiemer; Bart Immerzeel; Susanne Schneider; Keneilwe Sebola; Julie Coetzee; Mathieu Baldo; Gabrielle Thiebaut; Sabine Hilt; Jan Köhler; Sarah Faye Harpenslager; Jan E. Vermaat (Environmental Management, 2023)
Mass developments of macrophytes occur frequently worldwide and are often considered a nuisance when interfering with human activities. It is crucial to understand the drivers of this perception if we are to develop effective management strategies for ecosystems with macrophyte mass developments. Using a comprehensive survey spanning five sites with different macrophyte species in four countries (Norway, France, Germany and South Africa), we quantified the perception of macrophyte growth as a nuisance among residents and visitors, and for different recreational activities (swimming, boating, angling, appreciation of biodiversity, appreciation of landscape and birdwatching). We then used a Bayesian network approach to integrate the perception of nuisance with the consequences of plant removal. From the 1234 responses collected from the five sites, a range of 73–93% of the respondents across the sites considered macrophyte growth a nuisance at each site. Residents perceived macrophytes up to 23% more problematic than visitors. Environmental mindedness of respondents did not influence the perception of nuisance. Perceived nuisance of macrophytes was relatively similar for different recreational activities that were possible in each case study site, although we found some site-specific variation. Finally, we illustrate how Bayesian networks can be used to choose the best management option by balancing people’s perception of macrophyte growth with the potential consequences of macrophyte removal.

Sex-specific relationships between obesity, physical activity, and gray and white matter volume in cognitively unimpaired older adults - Brittany Intzandt; Safa Sanami; Julia Huck; Anne Labonté; Alexa Pichet Binette; Axel Mathieu; Cynthia Picard; Doris Dea; Claudio Cuello; Alan Evans; Christine Tardif; Gerhard Mulhaup; et al. (GeroScience, 2023)

Screening and Characterization of Some Lactobacillaceae for Detection of Cholesterol-Lowering Activities - Martin Frappier; Julie Auclair; Samir Bouasker; Sathursha Gunaratnam; Carine Diarra; Mathieu Millette (Probiotics and Antimicrobial Proteins, 2022)
Dyslipidemia, specifically abnormal levels of low-density lipoprotein cholesterol (LDL-C), is an important risk factor of cardiovascular disease. Evidence showing the promising abilities of probiotics to lower total cholesterol or LDL-C has, however, not yet convinced experts to recommend probiotic bacteria as treatment for blood lipid management. Therefore, there are opportunities for the development of new efficient cholesterol-lowering probiotics. Bile salt hydrolase (BSH) and feruloyl esterase (FAE) are bacterial enzymes proposed to explain the cholesterol-lowering capacity of some bacteria and have both been shown to be responsible for lipid reduction in vivo. Here, in order to select for cholesterol-lowering bacteria, 70 strains related to Lactobacillaceae were screened for BSH and FAE activities. Based on this two-way screening approach, two bacteria were selected and assessed for their capacity to assimilate cholesterol in vitro, another suggested mechanism. Lactobacillus acidophilus CL1285 showed BSH and FAE activity as well as capacity to assimilate cholesterol in vitro. Lactiplantibacillus plantarum CHOL-200 exhibited BSH activity and ability to assimilate cholesterol. These properties observed in vitro make both strains good probiotic candidates for the management of dyslipidemia. Further investigation is needed to assess their ability to reduce blood cholesterol in human trial.

How Raw and Gypsum Modified Bauxite Residues Affect Seed Germination, Enzyme Activities, and Root Development of Sinapis alba - Camille Fourrier; Mathieu Luglia; Catherine Keller; Pierre Hennebert; Julie Foulon; Jean-Paul Ambrosi; Bernard Angeletti; Stéven Criquet (Water, Air, & Soil Pollution, 2021)

Absence of QTc prolongation in a thorough QT study with imeglimin, a first in class oral agent for type 2 diabetes mellitus - Julie Dubourg; Sandrine Perrimond-Dauchy; Mathieu Felices; Sébastien Bolze; Pascal Voiriot; Pascale Fouqueray (European Journal of Clinical Pharmacology, 2020)

Impact of whole genome triplication on the evolutionary history and the functional dynamics of regulatory genes involved in Brassica self-incompatibility signalling pathway - Thanina Azibi; Houria Hadj-Arab; Maryse Lodé; Julie Ferreira de Carvalho; Gwenn Trotoux; Sylvie Nègre; Marie-Madeleine Gilet; Julien Boutte; Jérémy Lucas; Xavier Vekemans; Anne-Marie Chèvre; Mathieu Rousseau-Gueutin (Plant Reproduction, 2020)

Identifying genomic hotspots of differentiation and candidate genes involved in the adaptive divergence of pea aphid host races - Pierre Nouhaud; Mathieu Gautier; Anaïs Gouin; Julie Jaquiéry; Jean Peccoud; Fabrice Legeai; Lucie Mieuzet; Carole M. Smadja; Claire Lemaitre; Renaud Vitalis; Jean‐Christophe Simon (Molecular Ecology, 2018)
Identifying the genomic bases of adaptation to novel environments is a long‐term objective in evolutionary biology. Because genetic differentiation is expected to increase between locally adapted populations at the genes targeted by selection, scanning the genome for elevated levels of differentiation is a first step towards deciphering the genomic architecture underlying adaptive divergence. The pea aphid Acyrthosiphon pisum is a model of choice to address this question, as it forms a large complex of plant‐specialized races and cryptic species, resulting from recent adaptive radiation. Here, we characterized genomewide polymorphisms in three pea aphid races specialized on alfalfa, clover and pea crops, respectively, which we sequenced in pools ( poolseq ). Using a model‐based approach that explicitly accounts for selection, we identified 392 genomic hotspots of differentiation spanning 47.3 Mb and 2,484 genes (respectively, 9.12% of the genome size and 8.10% of its genes). Most of these highly differentiated regions were located on the autosomes, and overall differentiation was weaker on the X chromosome. Within these hotspots, high levels of absolute divergence between races suggest that these regions experienced less gene flow than the rest of the genome, most likely by contributing to reproductive isolation. Moreover, population‐specific analyses showed evidence of selection in every host race, depending on the hotspot considered. These hotspots were significantly enriched for candidate gene categories that control host–plant selection and use. These genes encode 48 salivary proteins, 14 gustatory receptors, 10 odorant receptors, five P450 cytochromes and one chemosensory protein, which represent promising candidates for the genetic basis of host–plant specialization and ecological isolation in the pea aphid complex. Altogether, our findings open new research directions towards functional studies, for validating the role of these genes on adaptive phenotypes.

Erratum to: Neural correlates of correct and failed response inhibition in heavy versus light social drinkers: an fMRI study during a go/no-go task by healthy participants - Salvatore Campanella; Julie Absil; Carina Carbia Sinde; Elisa Schroder; Philippe Peigneux; Mathieu Bourguignon; Mathieu Petieau; Thierry Metens; Mustapha Nouali; Serge Goldman; Guy Cheron; Paul Verbanck; et al. (Brain Imaging and Behavior, 2017)

Neural correlates of correct and failed response inhibition in heavy versus light social drinkers: an fMRI study during a go/no-go task by healthy participants - Salvatore Campanella; Julie Absil; Carina Carbia Sinde; Elisa Schroder; Philippe Peigneux; Mathieu Bourguignon; Mathieu Petieau; Thierry Metens; Mustapha Nouali; Serge Goldman; Guy Cheron; Paul Verbanck; et al. (Brain Imaging and Behavior, 2017)

Tropical Shearwater population stability at Reunion Island, despite light pollution - Benoit Gineste; Mathieu Souquet; François-Xavier Couzi; Yannick Giloux; Jean-Sébastien Philippe; Cedric Hoarau; Julie Tourmetz; Gaël Potin; Matthieu Le Corre (Journal of Ornithology, 2017)

Chemical composition of Melicope belahe (Baill.) T. G. Hartley (Rutaceae) leaf essential oil from Madagascar - Delphin J. R. Rabehaja; Gabriel Garcia; Julie-Marie Charmillon; Odile Désiré; Mathieu Paoli; Panja A.R. Ramanoelina; Félix Tomi (Natural Product Research, 2017)

Importance of Molecular Methods to Determine Whether a Probiotic is the Source of Lactobacillus Bacteremia - Alla Aroutcheva; Julie Auclair; Martin Frappier; Mathieu Millette; Karen Lolans; Danielle de Montigny; Serge Carrière; Stephen Sokalski; William E. Trick; Robert A. Weinstein (Probiotics and Antimicrobial Proteins, 2016)

Complete genomic sequence of barley (Hordeum vulgare) endornavirus (HvEV) determined by next-generation sequencing - Thierry Candresse; Armelle Marais; Roberto Sorrentino; Chantal Faure; Sébastien Theil; Valérie Cadot; Mathieu Rolland; Julie Villemot; Frank Rabenstein (Archives of Virology, 2016)

Intercomparison of statistical and dynamical downscaling models under the EURO- and MED-CORDEX initiative framework: present climate evaluations - Pradeebane Vaittinada Ayar; Mathieu Vrac; Sophie Bastin; Julie Carreau; Michel Déqué; Clemente Gallardo (Climate Dynamics, 2016)

Occurrence of 1,1′-dimethyl-4,4′-bipyridinium (Paraquat) in irrigated soil of the Lake Chad Basin, Niger - Marc Crampon; Yoann Copard; Guillaume Favreau; Julie Raux; Nadine Merlet-Machour; Mathieu Le Coz; Maïmouna Ibrahim; Valérie Peulon-Agasse; Florence Portet-Koltalo (Environmental Science and Pollution Research, 2014)

Truncating mutations in NRXN2 and NRXN1 in autism spectrum disorders and schizophrenia - Julie Gauthier; Tabrez J. Siddiqui; Peng Huashan; Daisaku Yokomaku; Fadi F. Hamdan; Nathalie Champagne; Mathieu Lapointe; Dan Spiegelman; Anne Noreau; Ronald G. Lafrenière; Ferid Fathalli; Ridha Joober; et al. (Human Genetics, 2011)

Seed exchanges, a key to analyze crop diversity dynamics in farmer-led on-farm conservation - Mathieu Thomas; Julie C. Dawson; Isabelle Goldringer; Christophe Bonneuil (Genetic Resources and Crop Evolution, 2011)

Movement reorganization to compensate for fatigue during sawing - Julie N. Côté; Pierre A. Mathieu; Mindy F. Levin; Anatol G. Feldman (Experimental Brain Research, 2002)